2008
DOI: 10.1002/imhj.20173
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the mother–infant relationship to dissociative, borderline, and conduct symptoms in young adulthood

Abstract: Recent high-risk longitudinal studies have documented a unique contribution of the quality of the early mother-child relationship to diverse forms of psychopathology in young adulthood, even with family economic status, later traumatic experiences, and some genetic factors controlled. In addition, measures of attachment-related deviations in caregiver-infant interaction predict more than measures of infant attachment behavior alone. This article reviews those findings in the context of cross-disciplinary think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 34 publications
7
111
0
7
Order By: Relevance
“…The Disinhibited subtype is characterised by indiscriminate friendliness which can be persistent and it has been suggested that this may be associated with personality problems in adult life (Lyons-Ruth, 2008). We have previously shown that children with indiscriminate friendliness can have complex neurodevelopmental problems and yet are frequently not engaged with therapeutic services (Kocovska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Disinhibited subtype is characterised by indiscriminate friendliness which can be persistent and it has been suggested that this may be associated with personality problems in adult life (Lyons-Ruth, 2008). We have previously shown that children with indiscriminate friendliness can have complex neurodevelopmental problems and yet are frequently not engaged with therapeutic services (Kocovska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Observan que la desconfianza en las madres resulta un elemento de riesgo para establecer unas relaciones de apego seguras, y que se asocia a sintomatología en los niños, con efectos a largo plazo. Dos años más tarde, Lyons-Ruth (2008), sigue insistiendo en la importancia de los patrones de apego en el desarrollo de psicopatología posterior. Matiza que más importante que el estilo de apego del niño, es el estudio de la interacción entre los patrones de apego de la madre y del niño.…”
Section: Relaciones Entre Estudios Empíricos En Psicología Del Desarrunclassified
“…A partir de lo que señalábamos anteriormente, se entiende la relación con muchos trastornos del comportamiento en niños, adolescentes y jóvenes. Finalmente, uno de los ámbitos más fértiles a nivel de investigación se encuentra en el estudio de la relación entre apego desorganizado infantil y los trastornos disociativos y borderlines en el adulto (15,16,12).…”
Section: El Apego Más Allá De Un Concepto Inspiradorunclassified
“…Esto explicaría su frecuente aparición en familias con un padre maltratador (casi 80% de los niños de estas familias). Lyons-Ruth amplió esta visión original, sugiriendo que el apego desorganizado también puede ser el producto de un padre extremadamente insensible o alterado que falla continuamente en tranquilizar y confortar la activación en el niño de las necesidades de apego (12); por tanto, el niño quedaría expuesto a la disregulación emocional sin contar con la ayuda de su cuidador. Main resumía estas situaciones hablando de cuidadores aterrorizados, aterrorizantes, y disociativos (7).…”
Section: Algunos Aspectos Teóricos Sobre Los Que Incidirunclassified
See 1 more Smart Citation